The effect of lottery scratch tickets and donation offers on response fraction: A study and meta-analysis - Boyle, T.; Heyworth, J.; Landrigan, J.; Mina, R.; Fritschi, Lin (Sage Publications, 2012)
Monetary incentives are the most effective way of increasing response to postal questionnaires; however, mailing currency is prohibited in many countries. Hence, nonmonetary incentives, such as lottery scratch tickets and donation offers, have been used. The effectiveness of different types of nonmonetary incentives is unclear, however. Two randomized controlled studies and meta-analyses were conducted to investigate the effect of two types of nonmonetary incentives on response. In the first study, the authors found that participants who received an unconditional lottery scratch ticket at invitation were 24% more likely to take part, while in the second study, the authors found that unconditional lottery scratch tickets and donation offers had a similar effect on response. The meta-analyses show that unconditional lottery scratch tickets significantly increase the chance of response by 9%, conditional scratch tickets have no effect, and donation offers cause a nonsignificant 4% increase in the chance of response. Unconditional lottery scratch tickets provide a modest increase in the likelihood of response.